LEAN MANUFACTURING DALAM UMKM UNTUK MENGURANGI WASTE, WAKTU, DAN BIAYA (STUDI KASUS PADA BISNIS ONLINE DREAMYSPACE) - Fernanda Rizki Brianti; Dian Anita Nuswantara (Journal of Innovation Research and Knowledge, 2024)
The purpose of this research is to analyze how the implementation of lean manufacturing can assess value-added, non-value-added, and minimize waste in the production process of Dreamyspace. This study focuses on Dreamyspace, an online business brand specializing in tote bags operating on an e-commerce platform. The analysis employed in this research includes value stream mapping, fishbone diagrams. The research findings indicate the presence of waste during the production process, including waiting time, unnecessary transportation, incorrect processing, excess inventory, unused employee activity, and defects. After improvements were made, the production time decreased from 124.17 minutes to 42.17 minutes.